Re-thinking sludge management within the Sustainable Development Goal 6.2. (1st June 2021) - Spinosa, L.; Doshi, P.
Abstract: Sustainable Development Goal 6.2 of the Agenda 2030 is addressed to achieve access to adequate and equitable sanitation and hygiene for all. Further, one of the major principles underlying the Lisbon Charter is that sustainable and safe management of wastewaters are fundamental to the health of communities and their sustainable socio-economic development. Within this framework, the management of sewage sludge in a sustainable manner is one of the critical issues facing modern society, due to the growing rise of its production, increasing difficulties in properly locating treatment and disposal works, and complying with more stringent environmental quality requirements, thus requiring a re-thinking of its management. This paper discusses major concepts and principles for re-thinking the sludge management in order to achieve the above-mentioned objectives. Highlights: Sludge management should be the starting-point when planning wastewater systems. Institutional and Governance aspects must be evaluated for effective re-thinking. A holistic view point shall be integrated while re-thinking sludge management. Need of procedures to reduce sludge amount, improve quality and maximize recoveries. Addressing wider challenges from technical viewpoints to the socio-economic reality.